A Simplified And Intuitive Visualization For Cardiopulmonary Exercise Testing Data...2021 ACSM Annual Meeting & World Congresses [Virtual], June 1-5, 2021 - Andonian, Brian J.; Hardy, Nicolas; Bendelac, Alon; Polys, Nicholas; Kraus, William E. (Medicine & Science in Sports & Exercise)
Cardiopulmonary exercise testing (CPET) is a powerful tool for determining a person's cause of exercise limitation. However, due to challenges in interpretation, and given the amount and complexity of data obtained, CPET is underutilized. PURPOSE: To address this problem, we evaluated novel CPET data visualizations to simplify initial diagnostic reasoning and interpretation for the patient with exertional dyspnea and exercise intolerance. METHODS: Using eight case examples from Wasserman's classic text Principles of exercise testing and interpretation, Fifth Edition, we evaluated formulas to define pulmonary, cardiac, and skeletal muscle limitations as percentages of optimal organ function. We implemented the formulas using the Python programming language; we used X3DOM, D3.js, and X_ITE to implement the visualizations. RESULTS: Pulmonary limitation was defined as the ratio of respiratory minute ventilation at peak exercise to maximum voluntary ventilation (VE/MVV). Cardiac limitation was defined as the difference in the slope of the O2 pulse (m) during the last quarter compared to the second quarter of the test. Skeletal muscle limitation was defined as the percentage of total exercise time after anaerobic or ventilatory threshold (VT) was reached. In all eight CPET case examples (case 1: normal man; case 2: normal athletic man; case 15: chronic heart failure; case 20: myocardial ischemia; case 47: severe emphysema; case 53: mild pulmonary asbestosis; case 66: mitochondrial myopathy; case 68: mixed disorder), the data visualization correctly identified the predominant exercise limitation associated with the established medical diagnosis. Visualizations are presented online (http://metagrid2.sv.vt.edu/~nickhrdy/cpet.html). CONCLUSIONS: To guide diagnostic evaluation and patient communication for the general practitioner, this novel 3D graphical presentation of CPET data simplifies conceptualization of organ system-specific exercise limitation. Further data integration of this CPET data visualization method in prospective patient populations and subsequent refinement of exercise limitation formulas are needed. The goal is to make CPET testing more accessible to the general medical provider and make the test of greater use in the medical toolbox.